Nematodos asociados a madera y arboles de coniferas en pinares españoles - Arias, M.=700 1 Escuer, M.; Bello, A.
(Es, En)
ilus., 15 ref.
Keywords: BURSAPHELENCHUS XYLOPHILUS; NEMATODA; ASERRADEROS; DISTRIBUCION GEOGRAFICA; PATOGENICIDAD; ESPAÑA